Is Dopamine an Iatrogenic Disruptor of Thyroid and Cortisol Function in the Extremely Premature Infant?. (4th June 2014) - Ng, Sze M.; Watson, Gabriella; Turner, Mark A.; Newland, Paul; Weindling, A. Michael
Abstract : Background . Dopamine is frequently used as an inotropic and vasoactive agent in neonatal intensive care units. Recent studies have reported that treatment with dopamine is associated with hypothyroxinaemia of prematurity. Objectives . The aim of this study was to determine if dopamine treatment in extremely premature infants altered thyroid and cortisol function. Methods . We prospectively measured plasma cortisol, TSH, free T4, total T4, and free triiodothyronine concentrations in babies born below 28 weeks' gestation within 5 days of birth, who were either treated with dopamine (D+) or who did not receive any dopamine (D−) within 12 hours of birth. Clinical Risk Index for Babies scores, lowest mean arterial pressure and highest plasma lactate concentrations in the first 12 hours, were recorded. Results . There were 78 babies included in the study (43 males). Mean gestational age was 25 weeks and 3 days (SD 1.3 weeks). Univariate analyses showed significant differences in cortisol and thyroid function between D+ and D−. Multivariable analyses showed that dopamine, gestation, and CRIB were independent factors affecting FT4 concentrations. No independent factors were shown to affect cortisol or TSH concentrations. Conclusion . Dopamine administration appeared to affect FT4 concentrations but not cortisol concentrations. The mechanisms are unclear but the effect does not appear to be related to hypotension or tissue underperfusion.